Reclaiming the Secular Glory: A Critical Study of Ayaz Rasool Nazki’s Satisar: The Valley of Demons - Chishti, Haadiyah; Romina Rashid (SARE: Southeast Asian Review of English, 2023)
Kashmir is known for diverse facets and elements, from its picturesque beauty to its age-old values and traditions passed down to generations. ‘Kashmiriyat’- a term often echoed to reverberate and reiterate the ethnic, nationalistic, and social consciousness of Kashmiris has been debated and discussed in different social, cultural, and literary circles. Ayaz Rasool Nazki’s maiden novel, Satisar: The Valley of Demons (2018), is a literary foray into the rich and glorious past of Kashmir with the undertones of repressive forces of anarchy, highlighting the destabilization of social and political equilibrium. It sheds light on the age-old cultural harmony and religious syncretism that once defined the geographical locale. The paper aims to present how literary output appeals to reclaim the secular glory lost to multiple political power structures over the years. Moreover, it will highlight the erosion of the rich cultural heritage that once delineated the essence of Kashmiriyat. The research objectives would be supported by a relevant theoretical framework to signify the importance of secularism in maintaining peace and stability in a pluralistic society like Kashmir. Keywords: Kashmiriyat, Secularism, Religion, Nationalism, Conflict